Korea n real estate market and boosting policies: Focusing on mortgage loans - Hwang, Sungjoo; Park, Moonseo; Lee, Hyun-Soo; Yoon, Yousang; Son, Bo-Sik (International Journal of Strategic Property Management, 2010)
The Korean real estate market is currently slowing down due to the global economic crisis, which resulted from subprime mortgage crisis in the United States. In response, the Korean government has adopted various policies in an attempt to deregulate real estate speculation. For example, the Loan to value ratio (LTV) has been increased in order to stimulate housing supply, demand, and housing transactions. However, these policies could potentially result in a mortgage crisis due to an increase in over‐amplified and high‐risk derivatives in Korea’s secondary mortgage market. Consequently, the housing market could fall into such deep confusion that it will be even more difficult to perform empirically based housing market forecasting. Therefore, a comprehensive and systematic method is required to analyze the real estate financial market and the causal relationships between market influence factors. With an integrated perspective and an application of a system dynamics methodology, this paper proposes Korean Real Estate and Mortgage Market dynamics models based on the fundamental principles and causal loops of housing markets, which are determined by the economic activities of consumers, financial agencies, and real estate financing investors. The potential effects of the Korean government’s deregulation policies are also considered by focusing on the main factor of these policies: the mortgage loan. First Published Online: 09 Jun 2011